PERAN WANITA PADA USAHA PENGOLAHAN IKAN ASAP DI KELURAHAN MANGGAR BARU KECAMATAN BALIKPAPAN TIMUR KOTA BALIKPAPAN - Melysah; Qoriah Saleha; Muhammad Syafril (Jurnal Pembangunan Perikanan dan Agribisnis, 2022)
The purpose of the study was to determine the motivation of women to work, analyze The Participation of women in decision making and analyze the contribution of women's income to family income in the smoked fish processing business. This research was conducted in Manggar Baru Village, East Balikpapan District, Balikpapan City. The sample used is the processing of smoked fish in Manggar Baru Village totaling 6 processors, the sampling method used is the census method. The data analysis method used is descriptive analysis method and income analysis. The results of this study indicate that women's motivation is divided into 2, namely internal ; driving factors the wife chooses to work because it is based on decisions that arise due to unfulfilled own desires and external ; driving factors the family is mutually supportive and helps in processing activities. The Participation of women in the production process is (100%), the husband's role in buying raw materials is (33%) and The Participation of husband and wife in strengthening capital is (33%). The Participation of women in making decisions to work in processing businesses ranging from investment/capital to fishery businesses, management of processing businesses to marketing of fishery products, wife's decision making is greater (67%). The contribution of women's income in helping to increase family income is high with an average of (80%). Keywords : Smoked Fish Processing, Women's Participation, Motivation, Decision Making, Income Contribution.